Denitrification losses from an intensively managed sub-tropical pasture – Impact of soil moisture on the partitioning of N2 and N2O emissions. (January 2016) - Friedl, Johannes; Scheer, Clemens; Rowlings, David W.; McIntosh, Heather V.; Strazzabosco, Alice; Warner, Daniel I.; Grace, Peter R.
Abstract: Intensively managed pastures in subtropical Australia under dairy production are nitrogen (N) loaded agro-ecosystems, with an increased pool of N available for denitrification. The magnitude of denitrification losses and N2 :N2 O partitioning in these agro-ecosystems is largely unknown, representing a major uncertainty when estimating total N loss and replacement. This study investigated the influence of different soil moisture contents on N2 and N2 O emissions from a subtropical dairy pasture in Queensland, Australia. Intact soil cores were incubated over 15 days at 80% and 100% water-filled pore space (WFPS), after the application of 15 N labelled nitrate, equivalent to 50 kg N ha −1 . This setup enabled the direct quantification of N2 and N2 O emissions following fertilisation using the 15 N gas flux method. The main product of denitrification in both treatments was N2 . N2 emissions exceeded N2 O emissions by a factor of 8 ± 1 at 80% WFPS and a factor of 17 ± 2 at 100% WFPS. The total amount of N-N2 lost over the incubation period was 21.27 kg ± 2.10 N2 -N ha −1 at 80% WFPS and 25.26 kg ± 2.79 kg ha −1 at 100% WFPS respectively. N2 emissions remained high at 100% WFPS, while related N2 O emissions decreased. At 80% WFPS, N2 emissions increased constantly over time while N2 O fluxes declined. Consequently, N2 /(N2  + N2 O) product ratios increased over the incubation period in both treatments. N2 /(N2  + N2 O) product ratios responded significantly to soil moisture, confirming WFPS as a key driver of denitrification. The substantial amount of fertiliser lost as N2 reveals the agronomic significance of denitrification as a major pathway of N loss for sub-tropical pastures at high WFPS and may explain the low fertiliser N use efficiency observed for these agro-ecosystems. Highlights: First study to quantify N2 from Australian pastures using the 15 N gas flux method. Nitrifier-denitrification contributed to N2 O emissions at high WFPS. N2 emitted accounted for a third of applied N fertiliser at high WFPS. These N2 losses are a significant loss of fertiliser N from subtropical pastures.